PENGARUH BIMBINGAN BELAJAR TERHADAP KECEMASAN SISWA DALAM MENGHADAPI UJIAN NASIONAL - Millatina, Amila (TALENTA, 2014)
Student anxiety in the face of National Examination is a fear of failure when the National  Examinations  can  do  well.  The  feeling  can  occur  because  of  a  lack  of preparation  optimal.Tujuan of this study was to investigate the influence of tutoring on student anxiety in the face of National Examination and to determine the level of anxiety of students in the face of the National Exam. The hypothesis is no influence of tutoring  on student anxiety in the face of the National Exam.The  subjects  used  in  this  study  were  male  and  female  students  MTsN  Tinawas Nogosari  Boyolali  class  IX.  Grouping  is  done  by  screening  participants.  The experimental group 1 is a group of private tutoring,  experimental group 2 is the regular tutoring  group  (group),  while  the  control  group  is  a  group  that  does  not  follow  the guidance  of  learning.  Participants  retrieval  techniques  using  non-random  sampling technique  is  purposive  sampling  techniques  ie  without  giving  an  equal  chance  on  the subject that are members of the population. Collecting data using the anxiety scale face the National Examination.Based on the analysis Anava KW between experimental groups 1, 2 experimental group and a control group of H =  12.817; p = 0.002 (p <0.01). This is also indicated by the  average  of  the  experimental  group  1  amounted  to  15.563,  then  the  average  of  the experimental group 2 at 24.656 and 33.281 average for the control group. These results prove the existence of differences between the experimental groups 1, experiment 2, and the control group, which means that there are differences in the level of anxiety among students  who  take  private tutoring  classes,  group  classes,  and  that  does  not  follow  the guidance of learning.